Legal Certainty of Property Law and Property Rights in Relation to Asta Cita's Prabowo Vision - Taufik Mappaenre; Martin Roestamy; Radif Khotamir Rusli; Asep Thobibudin Qolyubi (JURNAL ILMIAH LIVING LAW, 2025)
This study examines property law reforms under President Prabowo's administration, particularly through the lens of his vision, Asta Cita, which emphasizes economic transformation, regulatory efficiency, and inclusive governance. Indonesia faces significant challenges in land governance, such as overlapping regulations, conflicts between customary (adat) and national laws, and weak enforcement mechanisms. The administration aims to harmonize traditional and modern legal systems, streamline land registration, and foster investor confidence. The research analyses key legislative reforms, including the Omnibus Law on Job Creation and the Basic Agrarian Law, as well as case studies on property disputes. It finds progress in digitalizing land administration and simplifying land registration, but highlights persistent issues like fragmented policy implementation, inconsistent recognition of adat rights, and inadequate dispute resolution mechanisms. The study proposes solutions such as creating a unified land registry, improving national-regional coordination, and incentivizing faster dispute resolution to enhance property law effectiveness. However, it acknowledges the speculative nature of policy predictions and the lack of empirical data on land disputes, suggesting the need for further research. By offering both theoretical and practical insights, this study contributes to the discourse on Indonesia’s property law reforms and provides actionable recommendations for policymakers, legal professionals, and investors.